Unwelcome guests – the role of gland-associated Helicobacter pylori infection in gastric carcinogenesis - Beccaceci, Giulia; Sigal, Michael (Frontiers in Oncology, 2023)
Helicobacter pylori (H. pylori) are Gram-negative bacteria that cause chronic gastritis and are considered the main risk factor for the development of gastric cancer. H. pylori have evolved to survive the harsh luminal environment of the stomach and are known to cause damage and signaling aberrations in gastric epithelial cells, which can result in premalignant and malignant pathology. As well as colonizing the gastric mucus and surface epithelial cells, a subpopulation of H. pylori can invade deep into the gastric glands and directly interact with progenitor and stem cells. Gland colonization therefore bears the potential to cause direct injury to long-lived cells. Moreover, this bacterial subpopulation triggers a series of host responses that cause an enhanced proliferation of stem cells. Here, we review recent insights into how gastric gland colonization by H. pylori is established, the resulting pro-carcinogenic epithelial signaling alterations as well as new insights into stem cell responses to infection. Together these point towards a critical role of gland-associated H. pylori in the development of gastric cancer.